Plasmodium falciparum and soil-transmitted helminth co-infections among children in sub-Saharan Africa: a systematic review and meta-analysis - Degarege, Abraham (Parasit Vectors, 2016)
BACKGROUND: The epidemiology of soil-transmitted helminth (STH) and Plasmodium co-infections need better understanding. The findings of the individual studies are inconclusive. A systematic review was conducted to synthesize evidence on the association of STH infection with the prevalence and density of Plasmodium falciparum infection, and its effect on anaemia among children in sub-Saharan Africa (SSA). METHODS: Relevant studies published before March 6, 2015 were identified by searching Medline (via Pubmed), Embase, Cochrane Library and CINAHL without any language restriction. Studies on P. falciparum and STH co-infection among children in SSA except for case studies were included in this study. Studies were screened for eligibility and data extracted independently by two authors. The primary outcome assessed was the prevalence of P. falciparum infection and the secondary outcomes included P. falciparum density and prevalence of anaemia. Heterogeneity was assessed using Cochrane Q and Moran’s I(2) and publication bias was evaluated using Egger test. A random-effects model was used to estimate the summary odds ratio (OR) and the corresponding 95 % confidence intervals (CI). RESULTS: Out of 2985 articles screened, 11 articles were included in the systematic review; of these seven were considered in the meta-analysis. Of the 11 studies with 7458 study participants, seven were cross-sectional, one prospective cohort and three were randomized controlled trials. Four studies examined the outcome for hookworms, one for Ascaris lumbricoides and six for pooled (at least one) STH species. Eight studies measured prevalence/incidence of uncomplicated P. falciparum infection, two calculated prevalence of asymptomatic P. falciparum infection, three evaluated P. falciparum density and four considered prevalence of P. falciparum infection related anaemia/mean haemoglobin reduction. The odds of asymptomatic/uncomplicated P. falciparum infection were higher among children infected with STH than those uninfected with intestinal helminths (summary Odds Ratio [OR]: 1.4; 95 % Confidence Interval [CI]: 1.05–1.87; I(2) = 36.8 %). Plasmodium falciparum density tended to be higher among children infected with STH than those uninfected with intestinal helminths. However, STH infection was associated with lower odds of P. falciparum infection related anaemia (summary OR: 0.5; 95 % CI: 0.21–0.78; I(2) = 43.3 %). CONCLUSIONS: The findings suggest that STH infection may increase susceptibility to asymptomatic/uncomplicated P. falciparum infection but may protect malaria-related anaemia in children. Future studies should investigate the effect of STH infection upon the incidence of severe P. falciparum infection among children in SSA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1594-2) contains supplementary material, which is available to authorized users.